Managing Cooperation in Supply Network Structures and Small or Medium-sized Enterprises Main Criteria and Tools for Managers - Villa, Agostino; SpringerLink (Online service) (London : Springer London, 2011)
Managing Cooperation in Supply Network Structures and Small- or Medium-sized Enterprises outlines different approaches to the analysis of the organisation of small- or medium-sized enterprises (SMEs). Owing to the increased competition in the worldwide market, several SMEs operating in the same industrial sectors have agreed collaborative market strategies, both for raw material procurement and for final product delivery. The resulting networks, however, have a tendency to suffer from a lack of organization, which minimizes their impact on the product and labour markets, and causes a weak negotiation capacity within their supply chain. Managing Cooperation in Supply Network Structures and Small- or Medium-sized Enterprises aims to give managers of SMEs a simple methodology that helps them to understand when and why becoming a partner in an SME network can be profitable for their enterprise. It discusses the most critical organizational problems and identifies which procedures must be known to become a collaborative member of the network. Policy-makers, as well as managers and executives, will be able to appreciate the key issues in creating and managing healthy networks that serve global market requirements in the major industrial sectors. Managing Cooperation in Supply Network Structures and Small- or Medium-sized Enterprises enables them to evaluate the efficiency of their organization, and to estimate both the network performance and the opportunity for further development.
1. Organization in SME Networks -- 2. Cooperative Agreements for SME Network Organization -- 3. Collaboration Analysis for SME Networks -- 4. SME Networks and Clusters: An Approach for Their Performance Evaluation -- 5. Supply Network Structures and SMEs: Evidence from the International Clothing Industry.
Keywords: Engineering; Industrial engineering; Engineering economy; Business planning; Engineering; Industrial and Production Engineering; Organization/Planning.; Engineering Economics, Organization, Logistics, Marketing; Statistics for Engineering, Physics, Computer Science, Chemistry and Earth Sciences